Fabrication of stretchable antenna - Zailan, Zurain Nuridayu (Universiti Sains Malaysia, 2016)
Fabrication of stretchable antenna as an electronic device was used Polydimetyhlsiloxane (PDMS) as a substrate and silver ink acted as resonator which printed on the substrate. Other aim for this research is to analyze the performance of antenna working in transmitting and receiving the data in the best design. Two design have been proposed which giving different result for each of it. Design 1 and Design 2 different in the way of silver ink is printed. Design 1 giving no input matching signal while for Design 2 gave matching and wide bandwith result which make it suitable as an antenna. The resonant frequency is around 5.17 GHz. For efficiency frequency obtain from simulation is from 5.12 GHz to 5.26 GHz. for experimental, the resonant frequency is at 5.3 GHz and the efficiency frequency is from 4.4 GHz until 6.10 GHz. This antenna showing increase in conductivity when the length streched is increased. At same time, the properties of silicone as substrate and silver in fabrication of strechable antenna is been characterized in polymer and electronic properties by using FTIR, DSC, Hardness Shore A, Capacitance test, dan Dielectric constant. FTIR result showing the OH bond that already not exist due to completely cured. Dielectric constant for PDMS is from 2.3 to 2.9. PDMS also shows low capacitance value which make it suitable to be a substrate.